Transformasi kebudayaan Islam di Kotagede - Nasiwan Nasiwan (Universitas Negeri Yogyakarta, 2006)
This paper aims to investigate the main question: Is theory of cultural transformation formulated by Mitsuo Nakamura still significant after that Indonesian people experience fundamental changes in several aspect of their life? This paper is based on a qualitative research with case study approach. Data were collected by interview, observation, and document review. There are some main results of the research.l) Prediction of Mitsuo Nakamura which stated that subculture of santri in Kotagede has capability to lead changes, is still releant and valid due to their nowadays practices of life. While some part ofhis thoughts is notmore valid because some politictd configuration at national level occurs. 2) Cultural traniformation occurs in Kotagede; which is especially inspired and generatedby subculture of Modernist Islam. There is a phenomenon that value standard which was decidedby Majelis Tatjih Muhammadiyah is partially ignored.Approach of dakwah (religious proselytizing) got going to accommodate symbols and traditions ofsociety of Kotagede.